2021
DOI: 10.3390/v13122456
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteome Fingerprints Reveal Distinctiveness and Clinical Outcome of SARS-CoV-2 Infection

Abstract: Background: We evaluated how plasma proteomic signatures in patients with suspected COVID-19 can unravel the pathophysiology, and determine kinetics and clinical outcome of the infection. Methods: Plasma samples from patients presenting to the emergency department (ED) with symptoms of COVID-19 were stratified into: (1) patients with suspected COVID-19 that was not confirmed (n = 44); (2) non-hospitalized patients with confirmed COVID-19 (n = 44); (3) hospitalized patients with confirmed COVID-19 (n = 53) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Similar inflammatory markers were also detected by Bauer et al [ 38 ], analyzing with a PEA array the plasma proteome of 44 non-hospitalized and 53 hospitalized COVID-19 patients, and 44 non-COVID subjects. In fact, from the group comparison of COVID-19 vs. non-COVID-19, the authors identified 14 specific inflammatory proteins that can be related to SARS-CoV-2 infection, namely CXCL5, CXCL10, CXCL11, Gal-9, IL-18, IL-18R1, IFNγ, LIF-R, MCP-2, MCP-3, MERTK, MMP-1, PD-L1, and TNF.…”
Section: Proteomics Of Covid-19supporting
confidence: 75%
See 1 more Smart Citation
“…Similar inflammatory markers were also detected by Bauer et al [ 38 ], analyzing with a PEA array the plasma proteome of 44 non-hospitalized and 53 hospitalized COVID-19 patients, and 44 non-COVID subjects. In fact, from the group comparison of COVID-19 vs. non-COVID-19, the authors identified 14 specific inflammatory proteins that can be related to SARS-CoV-2 infection, namely CXCL5, CXCL10, CXCL11, Gal-9, IL-18, IL-18R1, IFNγ, LIF-R, MCP-2, MCP-3, MERTK, MMP-1, PD-L1, and TNF.…”
Section: Proteomics Of Covid-19supporting
confidence: 75%
“… The main findings obtained from the review of proteomics studies are summarized. In particular, the results from plasma [ 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ] and serum [ 43 , 44 , 45 , 46 , 47 , 83 , 86 ] studies were merged to identify the common proteins (top) that should represent the proteome signature of COVID-19. These protein entries were analyzed and clustered using STRING version 11.5, revealing the formation of three main clusters (bottom).…”
Section: Figurementioning
confidence: 99%
“…Finally, we assessed which variables were associated with disease severity that were shared in all the above-mentioned approaches ( Figure 5 f and Table 4 ). The relative Neutrophil count, together with the inflammatory markers MCP3 [ 50 ], IL6 [ 16 , 51 ], TRANCE [ 63 ], and MCP1 [ 24 ]; the neurology-associated markers CD200R1 [ 54 ] and MATN3 [ 54 ]; and the cardiometabolic marker LTBP2 [ 39 ] emerged in every analysis conducted. Lymphocyte count, KIT, and α2-MRAP [ 54 ] were shared by the four different feature correlation algorithms.…”
Section: Resultsmentioning
confidence: 99%
“…Proximity extension assay (PEA) is a high-throughput technology developed for the high-multiplex analysis of proteins, allowing a successful detection and quantification of several biomarkers [ 23 ] by incubating a low amount of the biological sample. To date, some comprehensive studies identifying sera biomarkers correlated with COVID-19 disease severity have been published [ 24 , 25 , 26 , 27 , 28 , 29 ], but only few of them [ 25 ] have employed machine learning techniques to reach a holistic view that summarizes an extensive clinical characterization (including demographic, comorbidity, clinical, and hematochemical data) of the patients with a large number of potential biomarkers in order to identify those that more effectively classify patients with adverse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the observation frequency of the protein alterations across independent studies might be considered as a reference of its reliability and its association with COVID-19. Of the regulated protein panel, thirty-four proteins have been also reported in five or more studies, twenty-four in two to five, and four were reported only in one study from other authors [ 10 , 11 , 12 , 13 , 14 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]; specifically, CD14, CRP, ITIH1, ITIH3, LBP, LRG1, SERPINA3, VWF, C9, ApoA1 and GSN have been associated with COVID-19 severity in at least eight independent studies ( Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%